Analisis Persepsi Masyarakat terhadap Keuangan Syariah di Indonesia - Zulmairoh, Aiza; Umida, Nur; Anggriani, Reni Ayu; Yuliana, Yuliana; Mawati, Wulan Anis (CV. Rayyan Dwi Bharata, 2025)
This research explores community perceptions of Islamic finance in Indonesia, a sector experiencing rapid growth. Given its Muslim-majority population, Indonesia encounters challenges in improving financial literacy and comprehension of Islamic finance principles among its citizens. Although there is significant interest in Islamic financial products, many individuals still lack a clear understanding of these concepts and their advantages. This study adopts a qualitative methodology, integrating literature reviews with in-depth interviews to gather insights on individual attitudes towards Islamic finance. The results reveal that Islamic finance is often seen as more equitable and ethical; however, skepticism and misconceptions remain prevalent and need to be addressed. Influencing factors such as education, culture, and media play crucial roles in shaping public views. This study emphasizes the importance of effective educational initiatives and outreach programs to enhance understanding and acceptance of Islamic finance, while also identifying the challenges Islamic financial institutions face in attracting clients. The success of this sector is vital not only for fostering economic development but also for empowering communities in accordance with Islamic values.